2019
DOI: 10.48550/arxiv.1909.05342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cops and robbers on directed and undirected abelian Cayley graphs

Peter Bradshaw,
Seyyed Aliasghar Hosseini,
Jérémie Turcotte

Abstract: We discuss the game of cops and robbers on abelian Cayley graphs. We improve the upper bound for cop number in the undirected case, and we give an upper bound for the directed version. We also construct Meyniel extremal families of graphs with cop number Θ( √ n).

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a similar flavor, Andreae [2] proved that excluding a graph H with t edges as a minor in a graph G implies that c(G) ≤ t. There are also cop number bounds for highly symmetrical graphs. For instance, Frankl [8] showed that normal Cayley graphs of degree d have cop number at most d. More recently, it was shown that abelian Cayley graphs on n vertices have cop number at most 0.95 √ n + 2 [7]. Lower bounds for cop number are also known for several graph classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar flavor, Andreae [2] proved that excluding a graph H with t edges as a minor in a graph G implies that c(G) ≤ t. There are also cop number bounds for highly symmetrical graphs. For instance, Frankl [8] showed that normal Cayley graphs of degree d have cop number at most d. More recently, it was shown that abelian Cayley graphs on n vertices have cop number at most 0.95 √ n + 2 [7]. Lower bounds for cop number are also known for several graph classes.…”
Section: Introductionmentioning
confidence: 99%
“…Lower bounds for cop number are also known for several graph classes. For instance, projective plane incidence graphs with 2q 2 + 2q + 2 vertices have cop number at least q + 1 [3], and certain abelian Cayley graphs on n vertices have cop number Ω( √ n), with some families achieving their cop number as high as 1 2 √ n [9,7]. Furthermore, Bollobás et al [4] and Pra lat and Wormald [17] showed that random graphs in G(n, p) have cop number of order Θ( √ n) a.a.s.…”
Section: Introductionmentioning
confidence: 99%